Digital Due Process Dilemma: A Study on the Application of the Principle of Legal Certainty in Ensuring Accountability and Data Protection in Indonesia's Digital Public Service Mall - Puja Alifpiya; Repania Nurrozaka; Wulandari Wulandari (Publikasi Indonesia, 2025)
This article analyzes the dilemma of applying the Asas Kepastian Hukum (Principle of Legal Certainty) within the acceleration of Mal Pelayanan Publik Digital (MPP Digital) in Indonesia. The rapid implementation of Automated Decision-Making (ADM) creates a critical tension between digital efficiency and the protection of citizens' Digital Human Rights (HAM Digital). Through a juridical-normative approach, the study identifies that the current administrative legal framework suffers from procedural ambiguity, particularly concerning the accountability of administrative decisions generated by algorithms. The failure to explicitly define Digital Due Process standards, such as the right to explanation and structured objection mechanisms undermines the legal certainty guaranteed by Law No. 30 of 2014 on Administrative Governance (UU AP). Furthermore, the lack of mandatory, auditable standards for data processing jeopardizes data integrity and protection, challenging the mandates of Law No. 27 of 2022 on Personal Data Protection (UU PDP). This research concludes that a robust, legally binding Digital Due Process framework is necessary to serve as the foundation for modern digital services, ensuring that technological progress is inseparable from administrative accountability and the fundamental rights of citizens.